Bullying : implications for the classroom - Sanders, Cheryl E.; Phye, Gary D. (Educational psychology., 2004)
In recent years there have been an increasing number of incidents where children have either perpetrated or been the victims of violence in the schools. Often times the children who perpetrated the violence had been the victims of school bullying. If bullying once was a matter of extorting lunch money from one's peers, it has since escalated into slander, sexual harassment, and violence. And the victims, unable to find relief, become depressed and/or violent in return. Despite all the media attention on recent school tragedies, many of which can be traced to bullied children, there has been little in the way of research-based books toward understanding why and how bullying occurs, the effects on all the individuals involved and the most effective intervention techniques. Summarizing research in education, social, developmental, and counseling psychology, Bullying: Implications for the Classroom examines the personality and background of both those who become bullies and those most likely to become their victims, how families, peers, and schools influence bullying behavior, and the most effective interventions in pre-school, primary and middle schools. Intended for researchers, educators, and professionals in related fields, this book provides an international review of research on bullying. KEY FEATURES: * Presents practical ideas regarding prevention/intervention of bullying * Covers theoretical views of bullying * Provides an international perspective on bullying * Discusses bullying similarities and differences in elementary and middle school * Presents practical ideas regarding prevention/intervention of bullying * Provides an international perspective on bullying * Outlines information regarding bullying during the elementary and middle school years * Covers theoretical views of bullying * Presents new approaches to explaining bullying * Contributing authors include internationally known researchers in the field.